Preparation method of phenolic resin synthesized by partially using PMI foam waste
By converting PMI foam waste into phenolic resin through alkaline treatment and reaction with phenol and formaldehyde, the method addresses environmental and economic challenges, achieving cost-effective and mechanically enhanced phenolic resin production.
Patent Information
- Application Number
- CN202411468861.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The disposal of PMI foam scraps and dust poses environmental challenges due to the lack of economical and environmentally friendly treatment methods, and the synthesis of phenolic resin is hindered by the high cost of phenol raw materials and mechanical limitations.
A method is developed to convert PMI foam waste into a phenolic resin by dissolving PMI dust in a sodium hydroxide solution, reacting it with phenol and formaldehyde to form a phenolic resin, reducing the amount of phenol and formaldehyde needed and enhancing mechanical properties through the incorporation of hexagonal structures.
This method recycles PMI foam waste, reduces production costs, and improves the mechanical properties of phenolic resin, enabling its use in various applications such as foaming materials and insulation materials.
Smart Images

Figure CN119161550A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin synthesis and application, in particular to a method for preparing a phenolic resin partially synthesized by using PMI foam waste. Background Art
[0002] Polymethacrylimide (PMI) foam has excellent mechanical properties and heat and pressure resistance, and is widely used in the field of high-performance composite sandwich materials. The preparation and application of PMI foam is to first polymerize unsaturated monomers into plate-like resins, and then heat and foam the plate-like resins in a baking device to obtain foam boards; the foam boards need to be peeled, cut, and processed to obtain the desired product shape. Due to its special foam preparation and processing utilization method, a large amount of scraps and dust will be generated. At present, no relatively economical and environmentally friendly treatment method has been found, and incineration and landfill will have an adverse impact on the environment. With the expansion of PMI foam market applications, the amount of PMI foam scraps and dust is also increasing. Finding an economical and environmentally friendly way to deal with a large amount of PMI scraps and dust has high economic value and important social significance. However, PMI foam is acid-resistant but not alkali-resistant. We directly transfer the dust collected by the vacuum cleaner into an alkaline solution, stir it thoroughly, and it can be completely dissolved in the alkali solution to form a transparent liquid.
[0003] The synthesis and application of phenolic resin has a long history. Due to its easy availability of raw materials, simple process equipment, good mechanical properties of products, heat resistance, cold resistance, insulation, dimensional stability, convenient molding and processing, flame retardancy and low smoke, phenolic resin has been widely used in the preparation of foaming materials, molded materials, laminated sheets, friction materials, insulation materials, grinding wheel resins, weather-resistant fiberboards, metal casting molds, and fiberglass molded materials adhesives, coatings, etc. In particular, phenolic foam prepared from thermosetting phenolic resin has fine pores and extremely low thermal conductivity, excellent anti-combustion performance, low smoke toxicity during combustion, stable size and chemical properties, and is known as the "king of thermal insulation materials". It is widely used in thermal insulation pipes in various industries such as construction, chemical industry, and shipbuilding. However, the synthesis of phenolic resin requires the use of relatively expensive phenol raw materials, which poses a certain obstacle to the economic efficiency of the product; and phenolic resin has large steric hindrance, short molecular chain length, and brittle material. It is necessary to use toughening resins and other means to improve mechanical properties, which also increases product costs.
[0004] PMI foam is a foam plastic with the best comprehensive performance. PMI dust is dissolved into liquid by sodium hydroxide solution and directly added to the raw materials of phenolic resin. The carboxyl structure in the PMI system undergoes condensation reaction with the hydroxymethyl of the phenolic resin, which can reduce the amount of phenol and formaldehyde added and save the production cost of phenolic resin. At the same time, the large amount of hexagonal structures in the PMI structure can improve the mechanical properties of phenolic resin. Different addition amounts have different improvement effects.
[0005] Based on this, a method for preparing a phenolic resin partially synthesized by using PMI foam waste is now provided, which can improve the performance of the existing phenolic resin and save production costs. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a phenolic resin synthesized partially using PMI foam waste, so as to solve the problems in the background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a phenolic resin partially synthesized using PMI foam waste comprises the following steps:
[0009] Step 1: Immerse the collected and processed PMI powder in a sodium hydroxide solution and stir continuously to turn the powder into a transparent solution;
[0010] Step 2: Add phenol solid to a three-necked flask or reactor equipped with jacket heating, titration funnel, temperature measurement, material stirring, and reflux condensation, heat to 45°C to melt it, add the above-mentioned PMI powder alkaline solution, continue stirring and reflux condensation; then add formaldehyde, slowly heat to 75°C, under heating conditions, phenol and formaldehyde and PMI liquid undergo condensation reaction, and react for 1 hour; slowly heat to 85°C and react for 1.5 hours; take samples every 10 minutes, and test the gel time at 150°C by a flat knife method; when the gel time reaches 100 seconds, add 85% phosphoric acid to neutralize the material to a pH value of about 6.5 to 7.4, vacuum to remove moisture, cool to 40°C, and discharge to obtain a transparent light brown liquid resin;
[0011] Step 3: Take samples to test the viscosity and solid content of the resin. Use a rotational viscometer to test the viscosity of the resin at 25°C. Place the sample in a watch glass and heat it at 105°C for 3 hours. Test the solid content of the resin. The resin with suitable viscosity and solid content is the resin for foaming.
[0012] On the basis of the above technical solution, the present invention also provides the following optional technical solution:
[0013] In an optional solution, the size of the PMI scrap powder is no larger than 3 mm to ensure that the powder is fully dissolved.
[0014] In an optional solution, the PMI scrap powder is soaked for no less than 4 hours, and the powder is not visible to the naked eye but appears as a transparent liquid.
[0015] In an optional solution, the phenol and formaldehyde only need 1 / 2 to 2 / 3 of the original amount.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. The present invention is to centrally process PMI scraps and dust, and convert them into liquid through alkalization treatment. Under alkaline heating conditions, the imide ring will be partially hydrolyzed to form carboxylic acid, and phenol and formaldehyde will react under alkaline heating conditions to form hydroxymethyl. The carboxylic acid will undergo esterification reaction with the hydroxymethyl, thereby increasing the molecular weight of the resin and improving the mechanical properties. PMI dust replaces a part of phenol and formaldehyde and is added to the raw materials for preparing phenolic resin, thereby realizing the reuse of PMI scrap powder, reducing the preparation cost of phenolic resin, and having economic value; at the same time, the structure of PMI contains a large number of hexacyclic rings, which can improve the mechanical properties of phenolic resin. Different phenolic resins can be prepared with different formula resins and different powder dosages, which can be applied in different fields and have the significance of environmental protection.
[0018] 2. The phenolic resin of the present invention is a water-soluble thermosetting resol phenolic resin, which can be used as a raw material for phenolic foam; by properly controlling the performance parameters of the resin, it can also be used as a molding material, laminated sheet material, insulating material, weather-resistant fiberboard, metal casting mold, and glue for glass fiber reinforced plastic molding material, coating material, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the schematic diagram of the reaction between phenol and formaldehyde;
[0020] Figure 2 The schematic diagram is a reaction principle diagram of the carboxyl structure in the PMI system of the present invention and the hydroxymethyl group of the phenolic resin. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0022] Example 1 Preparation of phenolic resin and phenolic foam without PMI powder
[0023] Step 1: Prepare liquid phenolic resin for foaming
[0024] Use a 500ml three-necked glass flask, equipped with a 100ml dropping funnel, an electric stirrer, a spherical condenser, an electric constant temperature water bath, and a thermometer. Add 94g of phenol solid and heat to 45°C to melt. Add 10g of 20% sodium hydroxide aqueous solution, continue stirring, reflux condensation. Add 146g of 37% formaldehyde aqueous solution, slowly heat to 75°C, react for 1 hour; slowly heat to 85°C, react for 1.5 hours; take samples every 10 minutes, and test the gel time at 150°C using the flat knife method; when the gel time reaches 100 seconds, add about 2.32g of 85% phosphoric acid to neutralize the material to a pH value of about 6.5 to 7.4, vacuum to remove about 58g of water, cool to 40°C, discharge, and obtain a transparent light brown liquid resin. The sample was placed in a watch glass and tested by heating at 105°C for 3 hours. The solid content of the resin was 82%. The viscosity of the resin at 25°C was 7000 mPa.s when tested by a rotational viscometer.
[0025] Step 2: Preparation of flame retardant thermal insulation phenolic foam
[0026] Take 100g of the above phenolic resin, add 16g of foaming agent (5g of dichloromethane, 6g of petroleum ether, 5g of cyclopentane), 8g of surfactant (DC-193), 8g of curing agent (2g of water, 2g of ethylene glycol, 0.5g of 98% sulfuric acid, 0.5g of p-toluenesulfonic acid, 3g of 85% phosphoric acid), mix and stir, pour into a mold at 65°C, seal, foam and cure for 2 hours. After cooling, demould to obtain a phenolic foam with fine and uniform pores.
[0027] After testing, the density of the phenolic foam is 60kg / m 3 , thermal conductivity is 0.032W / mK, compression strength is 0.16MPa, tensile strength is 0.18MPa, oxygen index is 36%. The foam has uniform and dense pores, low density, moderate strength, low thermal conductivity, and can achieve thermal insulation and flame retardancy.
[0028] Example 2 Preparation of phenolic resin and phenolic foam using PMI powder
[0029] Step 1: Prepare a sodium hydroxide solution of PMI powder
[0030] In a glass flask equipped with an electric stirrer, 40 g of PMI powder was placed, and 200 g of 15% sodium hydroxide solution was added. The mixture was stirred for about 5 hours to dissolve the powder and turn into a transparent solution.
[0031] Step 2: Prepare liquid phenolic resin for foaming
[0032] Use a 500ml three-necked glass flask, equipped with a 100ml dropping funnel, an electric stirrer, a spherical condenser, an electric constant temperature water bath, and a thermometer. Heat 62g of phenol solid to 45°C and melt. Add 17.2g of the alkaline aqueous solution of the above-mentioned PMI powder, continue stirring, and reflux condensation. Add 96g of a 37% formaldehyde aqueous solution. Slowly heat to 75°C and react for 1.5 hours; slowly heat to 85°C and react for 1.5 hours; take samples every 10 minutes and test the gel time at 150°C using a flat knife method; when the gel time reaches 100 seconds, add about 2.32g of 85% phosphoric acid to neutralize the material to a pH value of about 6.5 to 7.4, vacuum to remove about 83g of water, cool to 40°C, and discharge to obtain a transparent light brown-red liquid resin, which is a PMI-modified phenolic resin. The sample was placed in a watch glass and tested by heating at 105°C for 3 hours. The solid content of the resin was 81%. The viscosity of the resin was 7050 mPa.s when tested by a rotational viscometer at 25°C.
[0033] The reaction principle diagram of phenol and formaldehyde is as follows Figure 1 shown.
[0034] Step 3: Prepare the Insulating Phenolic Foam
[0035] Take 100g of the above phenolic resin, 16g of foaming agent (5g of dichloromethane, 6g of petroleum ether, 5g of cyclopentane), 8g of surfactant (DC-193), 8g of curing agent (2g of water, 2g of ethylene glycol, 0.5g of 98% sulfuric acid, 0.5g of p-toluenesulfonic acid, 3g of 85% phosphoric acid), mix and stir, pour into a mold at 65°C, seal, foam and cure for 2 hours. After cooling, demould to obtain a phenolic foam with fine and uniform pores.
[0036] After testing, the density of phenolic foam is 58kg / m 3 , thermal conductivity is 0.030W / mK, compressive strength is 0.19MPa, tensile strength is 0.2MPa, and oxygen index is 37%.
[0037] By adding an appropriate amount of alkaline solution of PMI powder, the carboxyl structure in the PMI system reacts with the hydroxymethyl of the phenolic resin to form a condensation reaction, and the amount of phenol and formaldehyde used is reduced, and the amount of phenol and formaldehyde added is about 2 / 3 of the original amount. The large amount of hexacyclic structures in the PMI structure enables the phenolic foam material to have good thermal insulation and flame retardant properties, and the mechanical properties are improved by about 10% compared with the phenolic foam in Example 1.
[0038] Example 3 Adjusting the amount of PMI powder and alkali solution to prepare phenolic resin and phenolic foam
[0039] Step 1: Prepare a sodium hydroxide solution of PMI powder
[0040] In a glass flask equipped with an electric stirrer, 35 g of PMI powder was placed, and 200 g of 12% sodium hydroxide solution was added. The mixture was stirred for about 5.5 hours to dissolve the powder and turn it into a transparent solution.
[0041] Step 2: Prepare liquid phenolic resin for foaming
[0042] Use a 500ml three-necked glass flask, equipped with a 100ml dropping funnel, an electric stirrer, a spherical condenser, an electric constant temperature water bath, and a thermometer. Heat 62g of phenol solid to 45°C, melt, and add to the three-necked flask. Add 21g of the alkaline aqueous solution of the above-mentioned PMI powder, continue stirring, and reflux condensation. Add 48g of solid polyformaldehyde, slowly heat to 75°C, react for 1 hour; slowly heat to 85°C, react for 1.5 hours; take samples every 10 minutes, and test the gel time at 150°C using the flat knife method; when the gel time reaches 90 seconds, add about 2.32g of 85% phosphoric acid to neutralize the material to a pH value of about 6.5 to 7.4, vacuum to remove about 42g of water, cool to 40°C, and discharge to obtain a transparent light brown-red liquid resin, which is a PMI-modified phenolic resin. The sample was placed in a watch glass and tested by heating at 105°C for 3 hours. The solid content of the resin was 82%. The viscosity of the resin was 7300 mPa.s when tested by a rotational viscometer at 25°C.
[0043] Step 3: Prepare the Insulating Phenolic Foam
[0044] Take 100g of the above-mentioned phenolic resin, 16g of a foaming agent (5g of dichloromethane, 6g of petroleum ether, 5g of cyclopentane), 8g of a surfactant (DC-193), and 8g of a curing agent (2g of water, 2g of ethylene glycol, 0.5g of 98% sulfuric acid, 0.5g of p-toluenesulfonic acid, and 3g of 85% phosphoric acid), mix and stir, pour into a mold at 65°C, seal, foam, and cure for 2 hours; demold after cooling to obtain a phenolic foam with fine and uniform pores.
[0045] After testing, the density of phenolic foam is 62kg / m 3 , thermal conductivity is 0.030W / mK, compressive strength is 0.20MPa, tensile strength is 0.22MPa, and oxygen index is 36%.
[0046] The dosage of phenol and formaldehyde remains unchanged, the dosage of PMI powder alkali solution is appropriately increased, and the same alkaline environment is maintained. The prepared phenolic foam material has good thermal insulation and flame retardant properties, and its mechanical properties are improved by about 20% compared with the phenolic foam in Example 1.
[0047] Example 4 Preparation of Abrasives and Grinding Tools Using PMI Powder and Water-Soluble Liquid Phenolic Resin
[0048] Step 1: Prepare a sodium hydroxide solution of PMI powder
[0049] In a glass flask equipped with an electric stirrer, 55 g of PMI powder was placed, and 200 g of 16% sodium hydroxide solution was added. The mixture was stirred for about 4.5 hours to dissolve the powder and turn it into a transparent solution.
[0050] Step 2: Preparation of liquid phenolic resin for abrasives
[0051] Use a 500ml three-necked glass flask, equipped with a 100ml dropping funnel, an electric stirrer, a spherical condenser, an electric constant temperature water bath, and a thermometer. Heat 100g of phenol solid to 45°C, melt it, and add it to the three-necked flask. Add 20g of the alkaline aqueous solution of the above-mentioned PMI powder, with a pH value of 11, continue stirring, and reflux condensation. Raise the temperature to 70°C, and drop 120g of 37% formaldehyde aqueous solution within 1 hour; react at a constant temperature for 1 hour; slowly raise the temperature to 90°C and react for 0.5 hours. Samples were taken every 10 minutes, and the gel time at 150°C was tested using the flat knife method. When the gel time reached 90 seconds, about 7.23 g of 85% phosphoric acid was added to neutralize the material to a pH value of about 6.5 to 7.4, and the temperature was lowered to below 40°C. 1 g of aminopropyltriethoxysilane and 1 g of urea were added, and the material was distilled under reduced pressure to a water content of 14%. The material was discharged to obtain a brown liquid phenolic resin, which was a PMI-modified phenolic resin. Tested at 25°C, the resin density was 1.18 g / cm 3 , viscosity 118mPa.s.
[0052] The resin is added with an appropriate amount of PMI powder alkali solution, which is fully integrated with the phenolic resin during the reaction process, and can effectively improve the comprehensive mechanical properties of the resin. It has low viscosity and is suitable for use in the abrasive tool industry. As a wet resin in the raw material, it can improve the strength and wear resistance of the prepared abrasive mold.
[0053] The principle diagram of the reaction between the carboxyl structure in the PMI system of the invention and the hydroxymethyl group of the phenolic resin is as follows: Figure 2 shown.
[0054] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a phenolic resin synthesized partially using PMI foam waste, characterized in that: The following steps are involved: Step 1: Immerse the collected and processed PMI powder in sodium hydroxide solution and stir continuously to turn the powder into a transparent liquid; Step 2: Add phenol solid to a three-necked flask or reactor equipped with jacket heating, titration funnel, temperature measurement, material stirring, and reflux condensation, heat to 45°C to melt it, add the above-mentioned PMI powder alkaline solution, continue stirring and reflux condensation; then add formaldehyde, slowly heat to 75°C, under heating conditions, phenol and formaldehyde and PMI liquid undergo condensation reaction, and react for 1 hour; slowly heat to 85°C and react for 1.5 hours; take samples every 10 minutes, and test the gel time at 150°C by a flat knife method; when the gel time reaches 100 seconds, add 85% phosphoric acid to neutralize the material to a pH value of about 6.5 to 7.4, vacuum to remove moisture, cool to 40°C, and discharge to obtain a transparent light brown liquid resin; Step 3: Take samples to test the viscosity and solid content of the resin. Use a rotational viscometer to test the viscosity of the resin at 25°C. Place the sample in a watch glass and heat it at 105°C for 3 hours. Test the solid content of the resin. The resin with suitable viscosity and solid content is the resin for foaming.
2. The method for preparing a phenolic resin synthesized partially using PMI foam waste according to claim 1, characterized in that: The size of the PMI scrap powder is no more than 3 mm.
3. The method for preparing a phenolic resin synthesized partially using PMI foam waste according to claim 1, characterized in that: The stirring and dissolving time of the PMI scrap powder is not less than 4 hours.
4. The method for preparing a phenolic resin synthesized partially using PMI foam waste according to claim 1, characterized in that: The phenol and formaldehyde only need 1 / 2 to 2 / 3 of the original amount.
Citation Information
Patent Citations
Production method of high-strength polymethacrylimide modified phenolic resin foam
CN103755905A
Polymethacrylimide foam and preparation method thereof
CN116120691A
